Livelihood Vulnerabilty of Reveriine Rural Dwellers: A Study in Morigaon, Assam - Pompi Bora, Ankur Boruah (International Journal of Modern Agriculture, 2020)
River bank erosion is an endemic and recurrent natural hazard in Assam. River bank erosion has its both direct and indirect impact on human being and socio-economic aspects of riverine people. Numerous vulnerabilities associated with flood and river bank erosion e.g. loss of homestead land, economic loss, shifting occupation, displacement etc. Morigaon is one of the most disaster prone districts of Assam. The riverine dwellers of Morigaon district face continuous riverbank erosion. The present paper is based on both primary and secondary data. The present study investigates the riverbank erosion hazards in Morigaon district and its impact on riverine people and livelihood vulnerability due to loss of land.